2011
DOI: 10.4103/0253-7613.77348
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemic activity of the leaf extract of Bischofia javanica blume on human leukemic cell lines

Abstract: Objective:Leaves of Bichofia javanica (BJ) have been traditionally used for many ailments including cancer. In the present study, antileukemic activity of the leaf extract was evaluated on human leukemic cell lines.Materials and Methods:Human leukemic cell lines U937, K562, and HL60 were purchased from National Facility for Animal Tissue and Cell Culture, Pune, India. The cells were routinely maintained in RPMI 1640 medium supplemented with 10% heat inactivated fetal calf serum. Cultures were maintained at 37º… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Cells were grown to about 70–80% confluency and subjected to H/R or normoxia with or without pre-treatment with EPO as described earlier. The cells were then washed with PBS and collected by centrifugation and stained with a combination of Acridine Orange (Ao) (100 µg/ml, Excitation 502 nm and Emission 526 nm);Ethidium Bromide (EtBr) (100 µg/ml, Excitation 510 nm and Emission 595 nm) 1∶1 ratio for 10 mins and 10µl of the cell suspension was taken on slide and fluorescent images were scanned using a confocal laser scanning [20] .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown to about 70–80% confluency and subjected to H/R or normoxia with or without pre-treatment with EPO as described earlier. The cells were then washed with PBS and collected by centrifugation and stained with a combination of Acridine Orange (Ao) (100 µg/ml, Excitation 502 nm and Emission 526 nm);Ethidium Bromide (EtBr) (100 µg/ml, Excitation 510 nm and Emission 595 nm) 1∶1 ratio for 10 mins and 10µl of the cell suspension was taken on slide and fluorescent images were scanned using a confocal laser scanning [20] .…”
Section: Methodsmentioning
confidence: 99%
“…Our data indicated that MBJ exhibits antioxidant and anti-inflammatory properties. Interestingly, quercetin and luteolin are known to have these effects [ 42 , 43 ] and are the major phytoconstituents of B. javanica [ 44 , 45 , 46 , 47 , 48 ]. Therefore, HPLC and DPPH analyses were conducted to verify the presence of these compounds in MBJ.…”
Section: Resultsmentioning
confidence: 99%
“…Menurut Prasad devi (2013), berdasarkan pengalaman masyarakat daun pepolo dapat mengatasi berbagai masalah kulit seperti luka bakar, dengan cara daun pepolo digiling sampai halus dan diaplikasikan pada kulit yang terkena luka bakar. Dari skrining fitokimia yang dilakukan Lingadurai (2011), daun pepolo mengandung senyawa alkaloid, sterol, triterpenoid, karbohidrat, protein, flavanoid, tannin, dan saponin. Beberapa penelitian juga telah dilakukan dan melaporkan adanya aktivitas dari daun pepolo sebagai antileukemia, antitusif, dan antinematoda (Rajbongsih, 2014).…”
Section: Pendahuluanunclassified